2001
DOI: 10.1002/1521-3773(20011203)40:23<4393::aid-anie4393>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis and Oxidative Properties of Polymer-Supported IBX

Abstract: Primary and secondary alcohols are oxidized smoothly under mild conditions and in high yields to the corresponding aldehydes and ketones by 1 (see scheme), the first polymer‐supported IBX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(46 citation statements)
references
References 11 publications
0
46
0
Order By: Relevance
“…Based on the remarkable acceleration of the oxidation of phenols by addition of only a small amount of iodoarene and documented examples of the reactions of iodoarene and Oxone ® , which produce pentavalent iodine species, [43][44][45][46][47][48] it was suggested that iodine(V) species, generated in situ, was included in this oxidation as the active catalyst. However, formation of pentavalent iodine species requires a higher temperature (70°C) than that in the oxidation of 2 with 1a and Oxone ® .…”
Section: Resultsmentioning
confidence: 99%
“…Based on the remarkable acceleration of the oxidation of phenols by addition of only a small amount of iodoarene and documented examples of the reactions of iodoarene and Oxone ® , which produce pentavalent iodine species, [43][44][45][46][47][48] it was suggested that iodine(V) species, generated in situ, was included in this oxidation as the active catalyst. However, formation of pentavalent iodine species requires a higher temperature (70°C) than that in the oxidation of 2 with 1a and Oxone ® .…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to mention that these observations together with the recent report on polymer-supported IBX 15 could be useful to develop green sequences toward biologically active steroids.…”
Section: Resultsmentioning
confidence: 87%
“…Prior studies have emphasized the use of a variety of insoluble supports for this purpose. 14 These previous studies have reported the use of both inorganic supports like silica gel 15 and organic polymer supports like crosslinked polystyrene. 16,17 These studies that immobilized IBX oxidants were precedented by earlier work by the Moss group who also immobilized iodosobenzoate reagents on polystyrene.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%